The nexus between Asian and US short-term financing rate - Rahman, Md. Saifur; Shahari, Farihana (Emerald Group Publishing Ltd., 2019)
Purpose: The purpose of this paper is to examine the nexus between Asian and the US short-term financing rates and compare them between pre- and post-Asian financial crisis. Design/methodology/approach: The short-term financing rate is used in the estimation by employing two-stage cointegration test. Findings: The result of the empirical study shows several outcomes; the short-term financing rates among the selected Asian countries are not highly correlated during pre-crisis period, but the rates become strongly associated during the post-crisis period. The US financing rate has significant influence on the Asian rate during both periods. Asian financing rates are not integrated by the influence of the USA, rather regional cooperation and financial initiatives lead the regional financing rate to be integrated. Originality/value: The empirical finding of the study offers significant policy implications for strengthening regional economic bonding and developing the financial systems. © 2019, Emerald Publishing Limited.